Rancangan Mesin Pemotong Kayu Menggunakan Rell Penggeser Dengan Motor Penggerak Daya 400 Watt - Moh Azizi Hakim; Erik Heriana; Zaenal Muttaqien; Sony Sukmara (Jurnal Teknik Mesin, 2022)
Large capacity cutting machines are rarely owned by some people because of the expensive machine prices, for small scale or home based industries, the problem in this study is the slow processing time, where they are required to be able to compete with large industries but only by relying on high-capacity cutting machines. small. Of the several existing cutting machines there are still deficiencies, so a modification of the slider is carried out. This refinement aims to be able to vary the cutting pattern in one motion. In this study using the reel method, where the sliding rail can rotate 1800. The cutting force that occurs is 61.6 N with a cutting speed of 324 m/s on yaku mahogany cutting media with an allowable bending of 10.4 kg/mm2. The recommended shaft diameter is based on a calculation of 5.7 mm, the shaft diameter used is 12 mm, with a fatigue safety factor value. and the allowable bending stress is 122.6 N/mm2, while the shear stress at the weld section is 1.33 N/mm2. This tool is very safe to use because the allowable shear stress is 122.6 N/mm2. As a result of this modification of the cutting tool, it was successful in making pieces of wood with varied patterns in one cutting motion and shorter processing time.